The Implementation of Drilling Method to Improve Vocabulary Mastery of Grade 7th Students at MTs. Mazra'atul Ulum Paciran - Nurul Badriyah Nurul Badriyah; Fiqih Aisyatul Farokhah (JELP Journal of English Language and Pedagogy, 2026)
This classroom action research aimed to improve the vocabulary mastery of seventh-grade students at MTs. Mazra'atul Ulum Paciran through the implementation of the drill method. The background of the study was students' low performance in vocabulary-related tasks and their lack of engagement in learning activities. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through pre-tests and post-tests. The pre-test results showed that the student’s average score was 63.51 (Absorptive Capacity 57%), indicating limited vocabulary mastery. In Cycle I, vocabulary was taught using repetition and memorization techniques. Cycle II incorporated multimedia tools and vocabulary-based games to enhance engagement. The post-test average score rose significantly to 80.89 (Absorptive Capacity 89%), demonstrating marked improvement. The findings suggest that the drill method is effective in enhancing vocabulary acquisition and student motivation in English language learning.